HASIL PENGEMBANGAN LEMBAR KERJA SISWA (LKS) EKSPERIMEN DAN NON-EKSPERIMEN BERBASIS INKUIRI TERSTRUKTUR PADA SUBPOKOK MATERI PERGESERAN KESETIMBANGAN KIMIA - MARYATI, Anita (2012)
This study aims to develop threestudent work sheets for structured inquiry based learning. They are an experimental student work sheet about change of concentration affecting chemical equilibrium and two non-experimentalstudent work sheets about change of pressure and temperature affecting chemical equilibrium. The method which used is Education Research and Development method with 4D model (define, design, develop, disseminate).The research instrumentsare interview guides, lab observation sheet, observation sheets learning, and questionnaires. The results of design step show that 0,1 M is minimum concentrate of FeCl3 solution and KSCN solution as reactants, and